Tirosine Kinase Inhibitors (TKI) Used in the Treatment of Non-Small Cell Lung Cancer (NSCLC) Based on Specific Genetic Alterations - Grigorescu, Alexandru Calin (Medical Science: Trends and Innovations Vol. 4, 2025)
This review aims to describe the main TKI inhibitor therapeutic agents used in targeted therapy of non-small cell lung cancer (NSCLC). Thus, we described: Osimertinib, Erlotinib, Gefitinib, Afatinib, Dacomitinib, Alectinib, Brigatinib, Lorlatinib, Crizotinib. Some observations were made on Entrectinib, although there is no experience in its use, among the molecular determinations approved for reimbursement in Romania is the determination of NTRK fusion, for which Entrectinib is recommended. A similar situation is with Dacomitinib. The side effects of these compounds that sometimes limit their use were briefly presented. Aspects relevant to clinical practice and no basic research nor pipeline research were briefly presented. In conclusion, it is demonstrated that for patients who have the appropriate mutations, deletions or gene fusions TKI represent an important role in the personalized therapy of patients with NSCLC.